Implementasi Kegiatan Keagamaan dan Peran Penting Masyarakat dalam Pilkada Desa Rena Panjang - Revola, Yashori; Abdul Rosyid Alkharomi, muhammad; Dewi, Trianita (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
The Real Work Lecture (KKN) activity carried out by UINFAS Bengkulu students batch 3 Group 111 in Rena Panjang Village, Lubuk Sandi District, Seluma Regency, took place from June 19, 2024 to August 3, 2024. This KKN aims to increase community participation in religious activities and simultaneous regional elections. This program includes activities to increase religious awareness through training and workshops, as well as socialization programs on the importance of participation in the regional elections. The methodology used involves a participatory and collaborative approach with community leaders and local stakeholders. The results of the activity showed an increase in public awareness and participation in religious activities and regional elections. This study concludes that a structured and community-based approach is effective in increasing community participation.